Nuclear Receptor Nur77 Deficiency Alters Dendritic Cell Function - Tel-Karthaus, Nina; Kers-Rebel, Esther D.; Looman, Maaike W.; Ichinose, Hiroshi; de Vries, Carlie J.; Ansems, Marleen (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are the professional antigen presenting cells of the immune system. Proper function of DCs is crucial to elicit an effective immune response against pathogens and to induce anti-tumor immunity. Different members of the nuclear receptor family of transcription factors have been reported to affect proper function of immune cells. Nur77 is a member of the NR4A subfamily of orphan nuclear receptors that is expressed and has a function within the immune system. We now show that Nur77 is expressed in different murine DCs subsets in vitro and ex vivo, in human monocyte derived DCs and in freshly isolated human BDCA1+ DCs, but its expression is dispensable for DC development in the spleen and lymph nodes. We show, by siRNA-mediated knockdown of Nur77 in human monocyte derived DCs and by using Nur77-/- murine DCs, that Nur77-deficient DCs have enhanced inflammatory responses leading to increased T cell proliferation. Treatment of human monocyte-derived DCs with 6-Mercaptopurine, an activator of Nur77, leads to diminished DC activation resulting in an impaired capacity to induce IFNγ production by allogeneic T cells. Altogether our data show a yet unexplored role for Nur77 in modifying the activation status of murine and human DCs. Ultimately, targeting Nur77 may prove to be efficacious in boosting or diminishing the activation status of DCs and may lead to the development of improved DC-based immunotherapies in respectively cancer treatment or treatment of autoimmune diseases.